TYPOLOGY OF BUILDINGS FOR DAIRY COWS IN BOSNIA AND HERZEGOVINA - Trkulja Tanja (Siberian Journal of Life Sciences and Agriculture, 2020)
In this paper, emphasis is on the clarification of existing models of dairy cows building (DBs) designs in Bosnia and Herzegovina (BA) in order to define their typology. The aim is to define the typologies of DBs with regard to existing design patterns and the analysis of the built objects. Several methodological procedures were applied in the collected data analysis. It is necessary to define the criteria for the classification of the DBs types and present a part of the results obtained during the conducted research. The criteria for this classification are: the productive herd size in DBs, base useful surface area of DBs; the form of the DBs base; the height of the DBs facade walls and the existence of roof openings on the DBs. Five main types and thirteen subtypes were marked. Their construction is complex and some design solutions (doors, loft area, height of the walls etc.) significantly determine the possibilities for further development of the farms.